Sumpia Product Development Using Labeling, Packaging and Marketing Home Industry Strategies - Wiwik Wida Safitri; Iza Hanifuddin (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2022)
This study to present the result of research on the labeling, packaging and marketing strategies of sumpia products in addition to the importance of improving quality in term of content, it also needs special attention from various parties such as the government, private sector, and universities. This business still uses traditional marketing systems and simple packaging. This research will focus on the implementation of labeling, packaging, and marketing strategies for sumpia products located in Sumberbening Village, Wates Hamlet, RT 34 RW 10, Balerejo District, Madiun Regency, East Java. The research method used is a qualitative method. This method tends to produce descriptive data and uses analysis. Meanwhile, for data collection obtained by observation, interviews, and documentation of the sumpia business. The results of the discussion show that the development of labeling, packaging, ang marketing strategies for sumpia products in Sumberbening Village, Wates Hamlet RT 34 RW 10 shows that the implementation of these activities has a positive impact on business. Even though it is still in the early stages, the progress is already looking better. The once ordinary packaging has become more valuable and many people have accepted the product. With the addition af product identity as an effort to provide product information and as a media or promotion place then by giving a taste variant of sumpia it is not in vain. Even more who like sumpia with the latest variant.